PENGARUH KEPATUHAN WAJIB PAJAK HOTEL DAN RESTORAN TERHADAP PENERIMAAN PAJAK DAERAH TAHUN 2017-2018 DI KABUPATEN OKU - Hasiatul Aini; Mardiah Kenamon; Isra Isra (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
This study aims to determine the effect of hotel and restaurant taxpayer compliance on2017-2018 regional tax revenue in OKU Regency. The analytical tool used in this study ismultiple linear regression. The results obtained partially in this study indicate that hoteltaxpayer compliance has no significant effect on OKU Regency tax revenue in 2017-2018with a tcount of -1,295 and restaurant taxpayer compliance also does not have a significanteffect on OKU Regency tax revenue in 2017 -2018 with a tcount of 0.482. Simultaneously,hotel and restaurant taxpayer compliance has no significant effect on OKU Regency taxrevenue in 2017-2018 with a Fcount of 0.986. The coefficient of determination (R Square)of 0.086 indicates that the contribution made by the variable compliance of hotel andrestaurant taxpayers to OKU Regency tax revenue in 2017-2018 is 8.6% while theremaining 91.4% is influenced by other variables not included into this research modelsuch as advertisement tax, entertainment tax, street lighting tax, nonmetallic mineral androck tax, parking tax and ground water tax.